Chemical Profiling of Locally Grown Zingiber officinale Roscoe (Ginger) Rhizomes using GC-MS and Biological Activities - Farhan, Abdillah Maulana; Ilmiah , Ika iffah; Mufidi, Farah Fakhirah; Perkasa, Excel Taruna Reksa; Shodiq, Muhammad Husein; Shodiq, Abdulloh Hasan (Life Science and Biotechnology, 2025)
Ginger (Zingiber officinale Roscoe), a widely used rhizomatous species of the family Zingiberaceae, possesses extensive medicinal value owing to its diverse phytochemical composition. This study aimed to characterize the bioactive constituents of locally grown ginger rhizomes using Gas Chromatography–Mass Spectrometry (GC–MS) to elucidate their potential pharmacological activities. GC–MS analysis enabled the detection of volatile and semi-volatile compounds based on retention time and molecular ion fragmentation patterns, providing a comprehensive chemical profile of the extract. A total of 39 compounds were identified, of which 14 exhibited relative abundances exceeding 3%. Major constituents included sesquiterpenes and phenolic derivatives known for their antioxidant, antimicrobial, anti-inflammatory, and anticancer properties. The presence of these bioactive metabolites confirms the therapeutic potential of Z. officinale as a natural source of bioactive agents and supports its continued exploration for pharmaceutical and nutraceutical applications